Histologically confirmed high-grade cervical intraepithelial neoplasia successfully treated with topical Paiteling: a two-case report - Li, Jing; Yang, Jie; Yu, Zhiying; Guan, Songqing (Frontiers in Medicine, 2025)
BackgroundHigh-grade cervical intraepithelial neoplasia (HSIL) threatens fertility-aged women worldwide. Surgical excision remains standard but may compromise future pregnancy. Paiteling, a multi-herbal topical preparation, has shown in vitro anti-HPV activity, yet clinical evidence is scant.Case presentationTwo reproductive-aged women with biopsy-proven HSIL refused loop electrosurgical excision. Biopsy slides were re-reviewed independently with p16 and Ki-67 immunostaining. Case 1 was CIN II and Case 2 was CIN III. Both patients received topical Paiteling (0.5 mL/lesion, three times weekly) plus 1% vaginal douche for 10 weeks.Intervention & outcomeLesions regressed completely within the treatment course. HPV-DNA testing confirmed HPV clearance by week 12. Follow-up colposcopy, cytology and directed biopsy remained negative at 12 months (Case 1) and 16 months (Case 2). Only mild transient vaginal burning occurred.ConclusionTopical Paiteling achieved histological and virological remission in two pathologically confirmed HSIL cases that declined excisional surgery. The findings suggest a fertility-preserving option worth systematic evaluation in prospective trials.